PENGARUH KEPERCAYAAN PADA SISTEM PEMERINTAHAN, DAN PENERAPAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Pattiruhu, Rosana; Nurhayati (Jurnal Nusa Akuntansi, 2025)
This study aims to analyze the factors influencing taxpayer compliance, focusing on the effect of Government Trust and E-Filing Implementation on Taxpayer Compliance. A quantitative approach was employed, using Structural Equation Modeling (SEM) through Partial Least Squares (PLS) with the help of SmartPLS software. Data were collected via questionnaires distributed to individual taxpayers and MSME actors. The results show that Government Trust does not have a significant effect on Taxpayer Compliance, with a coefficient value of 0.082. In contrast, E-Filing Implementation has a positive and significant effect on Taxpayer Compliance, with a coefficient of 0.500. The R² value of 0.295 indicates that both independent variables explain 29.5% of the variance in Taxpayer Compliance, while the remaining 70.5% is influenced by other variables outside the model. Validity and reliability tests show that all indicators meet the required criteria for outer loading, Composite Reliability (CR), and Average Variance Extracted (AVE). Overall, these findings suggest that improving the quality of digital-based tax services, such as e-filing, is more effective in enhancing taxpayer compliance compared to solely relying on public perception or trust in the government.